Dengue - Clinical Profile in Adults - NITHYALAKSHMI GAUDAM,; SANDHYA SURESH,; DR. PALANIANDAVAN, (International Journal of Pharma and Bio Sciences, 2018)
As there is a rise in Dengue fever in the recent years, there is a need to understand the various presentations of dengue fever. The aim is to study the clinical manifestations and laboratory findings of dengue fever. It is a prospective observational study on adult patients admitted and attending the outpatient clinic in Sree Balaji Medical hospital, Chennai. Two hundred and ten patients were analysed. All patients who were NS1 Antigen or IgM positive were included in the study. Clinical presentation, physical findings and laboratory parameters were studied. Of 210 patients, totally 126 males and 84 females presented with dengue fever. Among the clinical features, all patients had fever (100%), among others, myalgia and headache were predominant. The prominent physical findings were tachycardia (61.9%) and pleural effusion (61.9%). The most prominent hematological parameter was thrombocytopenia (87.6%). Dengue infection presents with varying clinical features. Various complications occur during the critical phase in dengue fever. In our study, acalculous cholecystitis (52%) was the most common complication noted. Timely identification and prompt fluid management are important in the management of dengue fever and close monitoring and treatment of the complications.